2010
DOI: 10.1007/s11284-010-0706-2
|View full text |Cite
|
Sign up to set email alerts
|

Strong light inhibits germination of Artemisia sphaerocephala and A. ordosica at low temperature and its relevance to revegetation in sandy lands of Inner Mongolia, China

Abstract: Strong light inhibits germination of Artemisia sphaerocephala and A. ordosica at low temperature and its relevance to revegetation in sandy lands of Inner Abstract Artemisia sphaerocephala and A. ordosica are two dominant shrub species in Mu Us sandy land (Inner Mongolia, China) and are widely used for vegetation restoration. However, there are two different conclusions about the effect of light on their germination: light promotes germination versus light inhibits germination. The aim of this study was to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…In our study, precipitation exhibited a significant negative correlation with C18:2 (-0.790) and a significant positive correlation with C24:1 (0.592). In addition, researchers have noted that an increase in altitude has tended to promote greater UFA content (with subsequently lower SFA content), possibly because altitude increases lead to lower temperatures and higher exposure to light (Dewhurst and King, 1998;Lai et al, 2010). However, this relationship is in contrast to the results of this study, which coincide with Vicia sativa by Mao et al, (2012) who found that other environmental factors besides temperature and light intensity, such as soil and air, may also influence the lipid metabolism of plants.…”
Section: Discussioncontrasting
confidence: 78%
“…In our study, precipitation exhibited a significant negative correlation with C18:2 (-0.790) and a significant positive correlation with C24:1 (0.592). In addition, researchers have noted that an increase in altitude has tended to promote greater UFA content (with subsequently lower SFA content), possibly because altitude increases lead to lower temperatures and higher exposure to light (Dewhurst and King, 1998;Lai et al, 2010). However, this relationship is in contrast to the results of this study, which coincide with Vicia sativa by Mao et al, (2012) who found that other environmental factors besides temperature and light intensity, such as soil and air, may also influence the lipid metabolism of plants.…”
Section: Discussioncontrasting
confidence: 78%
“…Thus, a dark requirement for germination would be adaptive for species distributed in sandy areas. Several studies have shown that the germination of many plants that inhabit sandy soils were stimulated by dark conditions ( Gutterman 1993 ; Zheng et al 2004 , 2005 a , b ; Lai et al 2010 ). In our study, the seeds of all seven species germinated well in the dark, indicating that burial in sand can increase the germination of these species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, seeds of the sandy-habitat species Trachyandra divaricata cannot germinate in red light ( Bell 1993 ), and germination of the two grass species Festuca hallii and Koeleria macrantha is strongly inhibited by light ( Federico et al 2014 ). Seeds of the sandy-land species Artemisia ordosica and Artemisia sphaerocephala only germinate in darkness ( Zheng et al , 2005 a , b ; Lai et al 2010 ). In sandy areas, seeds are often buried in sand at various depths, or they may disperse into shaded areas ( Maun 1998 ; Zheng et al 2005 c ).…”
Section: Introductionmentioning
confidence: 99%
“…where n represented the number of seeds being processed and G i represented the number of seeds germinating. A large GR value meant that seed germinated quickly (Lai et al., ; Zheng et al., ). All statistical analyses, including the test for homogeneity of variance, were performed using the SPSS 18.0 package (SPSS, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%